Beneath the stairs : [large type] a novel - Fawcett, Jennifer (Center Point Large Print, 2022)
"Few in sleepy Sumner's Mills have stumbled across the Octagon House hidden deep in the woods. Even fewer are brave enough to trespass. A man had killed his wife and two young daughters there, a shocking, gruesome crime that the sleepy upstate New York town tried to bury. One summer night, an emboldened fourteen-year-old Clare and her best friend, Abby, ventured into the Octagon House. Clare came out, but a piece of Abby never did. Twenty years later, an adult Clare receives word that Abby has attempted suicide at the Octagon House and now lies in a coma. With little to lose and still grieving after a personal tragedy, Clare returns to her roots to uncover the darkness responsible for Abby's accident."--